Activation of protein phosphatase 1 by a selective phosphatase disrupting peptide reduces sarcoplasmic reticulum Ca2+ leak in human heart failure - Fischer, Thomas Horst; Eiringhaus, Jörg; Dybkova, Nataliya; Saadatmand, Ali R.; Pabel, Steffen; Weber, Silvio; Wang, Yansong; Köhn, Maja; Tirilomis, Theodor; Ljubojevic, Senka; Renner, André; Gummert, Jan; et al. (European journal of heart failure, 2018)
Background Disruption of Ca2+ homeostasis is a key pathomechanism in heart failure. CaMKII-dependent hyperphosphorylation of ryanodine receptors in the sarcoplasmic reticulum (SR) increases the arrhythmogenic SR Ca2+ leak and depletes SR Ca2+ stores. The contribution of conversely acting serine/threonine phosphatases [protein phosphatase 1 (PP1) and 2A (PP2A)] is largely unknown. Methods and results Human myocardium from three groups of patients was investigated: (i) healthy controls (non-failing, NF, n = 8), (ii) compensated hypertrophy (Hy, n = 16), and (iii) end-stage heart failure (HF, n = 52). Expression of PP1 was unchanged in Hy but greater in HF compared to NF while its endogenous inhibitor-1 (I-1) was markedly lower expressed in both compared to NF, suggesting increased total PP1 activity. In contrast, PP2A expression was lower in Hy and HF compared to NF. Ca2+ homeostasis was severely disturbed in HF compared to Hy signified by a higher SR Ca2+ leak, lower systolic Ca2+ transients as well as a decreased SR Ca2+ load. Inhibition of PP1/PP2A by okadaic acid increased SR Ca2+ load and systolic Ca2+ transients but severely aggravated diastolic SR Ca2+ leak and cellular arrhythmias in Hy. Conversely, selective activation of PP1 by a PP1-disrupting peptide (PDP3) in HF potently reduced SR Ca2+ leak as well as cellular arrhythmias and, importantly, did not compromise systolic Ca2+ release and SR Ca2+ load. Conclusion This study is the first to functionally investigate the role of PP1/PP2A for Ca2+ homeostasis in diseased human myocardium. Our data indicate that a modulation of phosphatase activity potently impacts Ca2+ cycling properties. An activation of PP1 counteracts increased kinase activity in heart failure and successfully seals the arrhythmogenic SR Ca2+ leak. It may thus represent a promising future antiarrhythmic therapeutic approach.